PENGARUH PEMBERIAN ICE BREAKING TERHADAP MINAT BELAJAR MAHASISWA UNIVERSITAS MURNI TEGUH MEDAN - Rinaldi Batistuta Pandiangan; Harsudianto Silaen (PT. Hasba Edukasi Mandiri, 2025)
Background: Ice breaking is a game or activity that has the function of changing the atmosphere and can be understood as a physical game. Icebreaking also aims to create a dynamic learning atmosphere, full of interest and excitement so that it can create the joy of learning. serious but comfortable. when in the learning process. Learning gives a positive impression to students which can be achieved from various factors, one of which is student interest in learning. This means that interest has an important influence on learning If, students are less interested in learning, then at the end of the learning process students certainly do not understand what has been taught, therefore, the role of ice breaking is very important to eliminate boring situations during the learning process, and revive the atmosphere to be fresh, fun and build student interest in learning. Objective: To see the effect of ice breaking on learning interest of Universitas Murni Teguh students. Method: The type of research used by researchers is quantitative research. The method used is experimental with a research design using a quasi-experiment. The design used in this study is one group pre test and one group post test design and uses the Wilcoxon signed rank test with a total of 69 samples. Results: The results of this study indicate that there is an effect of giving ice breaking on the interest in learning of students at Universitas Murni Teguh Medan with a sig value. (2-tailed) 0.000 0.05. Conclusion: there is a significant effect in providing ice breaking on student interest in learning. where the post-test shows an increase in interest in learning.